(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article provides theoretical and practical information about modern solutions aimed at attracting students to the teaching process, which is one of the biggest problems of modern pedagogy, and focusing their attention on one point. Including modern educational platforms and their capabilities, places that can be used in the organization of the lesson process